EVALUATION OF THE DIVIDED ATTENTION CONDITION DURING FUNCTIONAL ANALYSES. Issue 1 (20th February 2013) - Fahmie, Tara A.; Iwata, Brian A.; Harper, Jill M.; Querim, Angie C.
Abstract A common condition included in most functional analyses (FAs) is the attention condition, in which the therapist ignores the client by engaging in a solitary activity (antecedent event) but delivers attention to the client contingent on problem behavior (consequent event). The divided attention condition is similar, except that the antecedent event consists of the therapist conversing with an adult confederate. We compared the typical and divided attention conditions to determine whether behavior in general (Study 1) and problem behavior in particular (Study 2) were more sensitive to one of the test conditions. Results showed that the divided attention condition resulted in faster acquisition or more efficient FA results for 2 of 9 subjects, suggesting that the divided attention condition could be considered a preferred condition when resources are available.